Influence of Hero Apical instruments on cleaning ovoid-shaped root canals - Renato Interliche; Melissa Andréia Marchesan; Silvio Rocha Correa da Silva; Jesus Djalma Pécora; Yara Teresinha Corrêa Silva-Sousa; Manoel Damião de Sousa-Neto (Sociedade Brasileira de Pesquisa Odontológica, 2011)
The cleaning capacity of Hero 642 nickel-titanium files, complemented by the Hero Apical instruments in flattened roots, was determined by histological analysis, considering the area of action of the instruments on the coronal walls and the presence of remaining debris. Twenty-four single-canal, human mandibular incisors were divided into three groups and prepared as follows: GI, instrumented with Hero 642 NiTi files 30/.06, 25/.06, 20/.06, 25/.06, and 30/.06; GII, instrumented as GI followed by Hero Apical size 30/.06; GIII, instrumented as GI followed by Hero Apical sizes 30/.06 and 30/.08, then returning to 30/.06 with pendulum movements. The apical thirds were prepared for histological processing, analyzed at 40× magnification and the images were examined morphometrically. Statistical analysis showed that GIII presented the best results for removing debris (5.22% ± 4.13), with more contact between the instruments and the root canal walls (19.31% ± 0.15). This differed statistically from GI (14.04% ± 4.96 debris removal, with 42.96% ± 7.11 instrument contact) and GII (12.62% ± 5.76 debris removal, with 35.01% ± 0.15 instrument contact). Root canal preparation with Hero 642, complemented by Hero Apical instruments (30/.06 and 30/.08, then re-instrumented with Hero Apical 30/.06 using pendulum movements), was more efficient for debris removal and allowed more contact of the instruments with the root canal walls. GII presented the worst results.